Mortalidade por doenças cerebrovasculares no estado do Paraná no ano de 2004 - Furukawa, Tatiane Sano (2008)
Introduction: Cerebrovascular diseases (CVD) are significant cause of morbidity and mortality in our country, which is leader in mortality of 45-year-old adults. Objective: The aim of this study was to analyze the mortality caused by Cerebrovascular diseases (CVD) of residents in the state of Paraná in 2004. Material and Method: Information available in the electronic address of Datasus of System of Information on Mortality (SIM/MS) was used. The population investigated consisted of residents in the state of Paraná aged 45 and over, who presented CVD, CID-10 from 160 to 169 (OMS, 2000a) as basic death cause. For the population data, the estimate of the demographic census-2004 was used (IBGE). Data were analyzed according to the variables sex, age, marital status, race/color, education, place of death, municipality of residence, home address and associated death causes. Calculations of proportion measures and mortality rates by 100,000 inhabitants were made. Results: In 2004, all over the state of Paraná, Diseases of the Circulatory System/Apparel (DSC) were responsible for 39.5% of deaths among people aged 45 years old and over; and among those deaths CVD were responsible for the largest number (32.8%). Mortality was higher in male sex, with approximately 54% of total deaths. The mortality coefficient was of 313.4 deaths per 100,000 inhabitants among men, and 247.6% among women. In relation to educational level, the investigation showed that the eldest black or brown individuals, presented lower levels of education, whereas those aged 75 and over (68.5%) had studied for up to 3 years. Among the black individuals, this percentile was of 78.7%, and it reached 79.2% among brown individuals. Deaths at home were more frequent among black individuals aged 65 and over -with up to 3 years of education, who lived in the municipal districts that were not the main health center. Moreover, those municipal districts also presented a mortality coefficient 10% higher than the municipalities with health centers and showed higher level of deaths among the black and brown individuals (15.3%) whose level of education was lower - 73.5% of deaths of individuals with 3 or up to 3 years of formal education. Regarding the analysis of mortality due to multiple causes, an average of 2.94 informed diagnoses was verified, in the Death Reports, with small difference between male or female. Among the causes associated to deaths, DAC was emphasized in 55.5% of the death reports, in which 67.5% referred to hypertensive diseases, whereas respiratory diseases accounted for 46.5% of the reports. Conclusions: The results of the present investigation corroborate results of previous studies and reinforce the hypothesis concerning the importance of developing actions pro-reduction of mortality levels by CVD, as observed. In addition, the results suggest different accesses to individual and community health, according to the level of economical development of the areas in the state of Paraná. Hypertension, presented as cause associated to death by CVD, emphasizes the relevance of having access to prevention and control of the disease, with consequent decrease in mortality by CVD. Therefore, the planning of specific actions for controlling CVD should be high priority in areas of larger risk, as well as in areas whose population present lower socioeconomic levels.